Preliminary report on the faunal remains from Aragatsavan 1, Armenia - Zarikian, Noushig; Manukyan, Sona; Vardanyan, Benik; Shakhmuradyan, Mariam (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
This paper presents the preliminary analysis of the zooarchaeological data from the settlement of Aragatsavan 1, Armenia. The excavation of the site is in progress and a complete stratigraphic sequence has not been obtained yet, while the excavated levels are dated to the second and third phases of the Trialeti-Vanadzor culture of the Middle Bronze Age period (19th -18/17th centuries BC). Taxonomic and metric analyses suggest that all the species are domestic. Sheep (Ovis aries) and goats (Capra hircus) constitute more than half of the number of identified specimens (NISP), followed by horses (Equus caballus) and cattle (Bos taurus). Pigs (Sus scrofa domesticus) are scarce. Butchery and cut marks have been detected on many of the samples. A certain proportion of bones is burnt. As zooarchaeological data are not numerous for the Middle Bronze Age period of Armenia and South Caucasus, the faunal remains from Aragatsavan 1 are important. They provide new information on the subsistence economy in the region during the 3rd - 2nd millennia BC.